Multiferroic‐Enabled Magnetic‐Excitons in 2D Quantum‐Entangled Van der Waals Antiferromagnet NiI2 (Adv. Mater. 10/2022). Issue 10 (10th March 2022) - Son, Suhan; Lee, Youjin; Kim, Jae Ha; Kim, Beom Hyun; Kim, Chaebin; Na, Woongki; Ju, Hwiin; Park, Sudong; Nag, Abhishek; Zhou, Ke‐Jin; Son, Young‐Woo; Kim, Hyeongdo; et al.
Abstract : Multiferroic Materials In article number 2109144, Jae Hoon Kim, Je‐Geun Park, and co‐workers report a new exciton in multiferroic NiI2, consisting of a 2D triangular lattice. This newly discovered exciton is not only magnetic but also quantum entangled. When an electron and hole combine via a transition between two quantum‐entangled states, it produces a bright reddish light of 1.384 eV.